The rottenest angel - Stine, R. L.; Park, Trip (New York HarperCollins, 2007)
Everyone at Rotten School loves new student Angel Goodeboy. But as Bernie Bridges discovers, when the teachers aren't watching, his new roommate is no angel.
"A Parachute Press book."
Includes an excerpt from book #11, Punk'd and skunked.
Keywords: Boarding schools -- Juvenile fiction; Boarding school students -- Juvenile fiction; Schools -- Juvenile fiction